Edukasi Kepada Ibu Tentang Pengenalan dan Upaya Deteksi Dini Kanker Leher Rahim (Serviks) - Lusiatun Lusiatun; Imarina Tarigan (CV. ALIM'SPUBLISHING, 2025)
Cervical cancer is one of the most common types of cancer in women after breast cancer. Cervical cancer is the most common cause of morbidity and mortality in women throughout the world. Cervical cancer if diagnosed and treated in the early stages of the disease can be cured. So recognizing the symptoms and checking with a health professional to solve the problem is an important step. This community service aims to provide education and understanding to mothers about cervical cancer as well as efforts to detect cervical cancer early. Community service activities were carried out in Sungai Jernih Hamlet RT 10 Ladang Peris Village, Batanghari Regency. The activity was carried out using the lecture method, followed by questions and answers about cervical cancer. This activity was attended by 32 women in the RT 10 Dusun Sungai Jernih area. There was an increase in maternal knowledge between before and after being given education, namely before education from 62.5% in the poor category and 37.5% in the good category to 75% in the good category and 25% in the poor category.